Improved differential voltage-to-frequency converter for telemetry - Thepmanee, Teerawat; Julsereewong, Amphawan; Sangsuwan, Thaksin (My University, 2010)
An improved differential voltage-to-frequency converter (dVFC) for telemetry is presented. The proposed method employs op-amps in conjunction with current conveyors and Set-Reset latch. Surpassing the previous dVFC using only current conveyors and Set-Reset latch, the proposed configuration affords significant improvement in accuracy. Experimental results are used to verify the good operation characteristics of the proposed dVFC.